DPP-4 Inhibitors as Potential Candidates for Antihypertensive Therapy: Improving Vascular Inflammation and Assisting the Action of Traditional Antihypertensive Drugs - Zhang, Jianqiang; Chen, Qiuyue; Zhong, Jixin; Liu, Chaohong; Zheng, Bing; Gong, Quan (Frontiers in Immunology, 2019)
Dipeptidyl peptidase-4 (DPP-4) is an important protease that is widely expressed on the surface of human cells and plays a key role in immune-regulation, inflammation, oxidative stress, cell adhesion and apoptosis by targeting different substrates. DPP-4 inhibitors (DPP-4i) are commonly used as hypoglycemic agents. However, in addition to their hypoglycemic effect, DPP-4i have also shown potent activities in the cardiovascular system, particularly in the regulation of blood pressure (BP). Previous studies have shown that the regulatory actions of DPP-4i in controlling BP are complex and that the mechanisms involved include the functional activities of the nerves, kidneys, hormones, blood vessels and insulin. Recent work has also shown that inflammation is closely associated with the elevation of BP, and that the inhibition of DPP-4 can reduce BP by regulating the function of the immune system, by reducing inflammatory reactions and by improving oxidative stress. In this review, we describe the potential anti-hypertensive effects of DPP-4i and discuss potential new anti-hypertensive therapies. Our analysis indicated that DPP-4i treatment has a mild anti-hypertensive effect as a monotherapy and causes a significant reduction in BP when used in combined treatments. However, the combination of DPP-4i with high-dose angiotensin converting enzyme inhibitors (ACEI) can lead to increased BP. We suggest that DPP-4i improves vascular endothelial function in hypertensive patients by suppressing inflammatory responses and by alleviating oxidative stress. In addition, DPP-4i can also regulate BP by activating the sympathetic nervous system, interfering with the renin angiotensin aldosterone system (RAAS), regulating Na/H2O metabolism and attenuating insulin resistance (IR).